Lived Experiences of Chronic Kidney Disease Patients undergoing Haemodialysis in a Tertiary Hospital of Nepal - Sah, Bimala Kumari; Khan, Imran; Dhungana, Ashesh; Subedi, Madhusudan; Dhital , Rolina (Journal of Nepal Health Research Council, 2025)
Background: Chronic kidney disease (CKD) poses significant global health challenges, including in Nepal, where the increasing need for hemodialysis are influencing patient’s daily life. This study aimed to explore lived experiences of CKD patients undergoing hemodialysis. Methods: A qualitative, phenomenological research design was employed. In-depth interviews were conducted with 13 hemodialysis patients at Bir Hospital from December, 2023 to January, 2024. Analysis followed Colaizzi’s method, ensuring data quality through established credibility and transferability measures. Results: Four major themes emerged: (i) Journey to receive hemodialysis (ii) Financial Constraints (iii) Psychosocial support (iv) Seeking for special health services. Patients perceived hemodialysis as a hope for existence but faced financial troubles and inadequate special and psychosocial support. Conclusions: The lived experiences of the patients reflected both hope and challenges highlighting the need for improved health services and counseling in hemodialysis wards, along with enhanced governance in the healthcare system. Keywords: Chronic kidney disease; hemodialysis; lived experience; pilot; qualitative.